Pseudo-hypotension with acute pulmonary oedema due to simultaneous bilateral subclavian artery stenosis in a patient with coronary artery bypass graft surgery using bilateral internal mammary arteries: a case report. Issue 5 (31st May 2019) - Hirata, Kazuhito; Nakazato, Jun; Wake, Minoru; Takahashi, Takanori
Abstract: A 75-year-old woman, with a history of bilateral internal mammary artery–coronary artery bypass graft surgery, developed hypotension and pulmonary oedema posing as cardiogenic shock. Severe bilateral subclavian artery stenosis emerged to be the cause of ischaemic myocardial dysfunction and heart failure. An emergency endovascular treatment was successfully performed. The presence of simultaneous bilateral subclavian artery narrowing as the pathophysiologic mechanism of myocardial ischaemia makes this case remarkable.